Digital Transformation And Innovation In The Digitalization Era To Improve Organizational Culture - Fatchurrohman, Mochamad; Supriadi, Iman; Alfiyatussholichah, Alfiyatussholichah; Wardhani, Parwita Setya (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
The advancement of digital technology has significantly influenced various aspects of organizational operations in today’s digitalization era. Digital transformation and innovation have emerged as critical concepts in fostering an organizational culture that is adaptive, innovative, and responsive to change. This study adopts a qualitative approach through a case study method and literature review as its theoretical foundation, aiming to explore the influence of digital transformation and innovation on organizational culture in depth. The findings reveal that digital transformation has a notable impact on organizational culture, with both positive and negative implications. On the positive side, it enhances performance through automation, accelerated data processing, and changes in work processes, thereby improving productivity and work quality key indicators of a strong organizational culture. Moreover, the integration of digital communication and collaboration tools enables employees to actively share ideas, collaborate in teams, and engage in virtual work environments. However, the study also identifies several challenges, including technological and infrastructure limitations, constrained resources, inadequate policy support, entrenched corporate culture, and resistance to change. Effective change management in digital transformation and cultural innovation requires strong leadership, targeted education and training, transparent communication, the mitigation of fear and resistance, as well as ongoing measurement and evaluation. Successful digital transformation depends on the synergy between technology, people, and a continuously evolving organizational culture.